1996
DOI: 10.1051/forest:19960224
|View full text |Cite
|
Sign up to set email alerts
|

Oaks in a high-CO2 world

Abstract: Summary — The concentration of carbon dioxide in the atmosphere is one environmental factor that is certain to influence the physiology and productivity of oak trees everywhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
3
12
0
1
Order By: Relevance
“…For instance, Quercus rubra (oak) had twice the rate of isoprene emission when grown in twice current CO 2 concentration, wheras in Populus tremuloides (aspen) the release was reduced by 30–40% (). Similar responses for oak are reported by Norby (1996) and Tognetti et al (1998). VOC emissions play an important role as tropospheric‐ozone precursors.…”
Section: Co2 and Trace Gas Emmissionsupporting
confidence: 89%
See 2 more Smart Citations
“…For instance, Quercus rubra (oak) had twice the rate of isoprene emission when grown in twice current CO 2 concentration, wheras in Populus tremuloides (aspen) the release was reduced by 30–40% (). Similar responses for oak are reported by Norby (1996) and Tognetti et al (1998). VOC emissions play an important role as tropospheric‐ozone precursors.…”
Section: Co2 and Trace Gas Emmissionsupporting
confidence: 89%
“…The N response disappeared when TNC was subtracted from dry mass. However, in a number of other studies N reduction goes beyond a dilution signal, suggesting some reduction of leaf protein, most likely associated with photosynthetic downward adjustment (e.g., Gifford et al 1996, Norby 1996, Poorter et al 1997, Penuelas and Estiarte 1998). The response can be induced very rapidly as was shown in short‐term CO 2 ‐enrichment in tropical‐forest tree canopies (Würth et al 1998) suggesting, once more, a leaf‐tissue‐specific answer to CO 2 enrichment rather than an overall system response as explanation (Körner and Arnone 1992, Körner et al 1995).…”
Section: Tissue Quality Consumers and Recyclingmentioning
confidence: 96%
See 1 more Smart Citation
“…An acceleration of this tendency since 1940 was also observed by Becker et al (1994) and Badeau et al (1995) on Fagus sylvatica in northeastern France. This radial growth improvement has often been related to changes in environmental factors, such as average temperature in some cases, or more often atmospheric CO 2 and N deposition (Kenk and Fischer 1988;Graumlich 1991;Norby 1996;Spiecker et al 1996;Jacoby and D'Arrigo 1997). Changes in silvicultural practices in managed forests, with stronger and more frequent thinnings in the young forest stands, could also be responsible for a higher radial growth of the dominant trees (Becker 1989;Becker et al 1995;Schneider and Hartmann 1996;Spiecker et al 1996).…”
Section: Discussionmentioning
confidence: 93%
“…(Cotrufo et al 1998a;Coûteaux et al 1999;O'Neill and Norby 1996). Although some individual experiments have documented statistically significant declines in [N] in CO 2 -enriched leaf litter (e.g., Cotrufo and Ineson 1996;Cotrufo et al 1994), very few experiments with plants rooted in the ground have done so, and O'Neill and Norby (1996) concluded that the responses of litter chemistry of plants grown in pots or in growth chambers may be artifactual. In fact, because , v v exposed in solardomes.}…”
Section: Litter Decomposition -Co 2 Releasementioning
confidence: 96%